Nota sobre el uso de la documentación parlamentaria del congreso de los diputados en internet - Gonzalo Rozas, Miguel Ángel (Revista General de Información y Documentación, 2002)
An analysis is made of the data pertaining to the queries made in the 7th Legislature to the Spanish parliament´s official publications available on the Web site of the Congreso de los Diputados.The users have for the most part downloaded the publications from the A Series of the Official Parliamentary Bulletin, Congress Section which is dedicated to the bills whereas the consultation of other series is much less; likewise the examination of the Journal of Debates is in relation with the parliamentary procedure of legislative initiatives. The studies concerning the use of information on the Internet enable information needs to be identified and the efficiency of information retrieval from Web pages to be improved.
Keywords: Spanish Parlament; Internet; Official Publications